Diffusing the legal conceptions of the global south and decolonizing international law: crystallizing animal rights through inter-judicial dialogue - Hall, Catherine (Frontiers in Animal Science, 2023)
Global environmental law is characterized by Eurocentric cultural paradigms that perceive humanity as external and superior to Nature. This supremacy over Nature reflects a legacy of Western colonial domination. Accordingly, environmental regulations have been complicit in sustaining the paradigms that have given rise to the Anthropocene. It is against this backdrop that this article seeks to investigate how global environmental law could engage in transformative reform by embracing Southern epistemologies, particularly through the legal subjectivisation of Nature, i.e. by conceptualizing Nature as subjects of rights. Rooted in Indigenous worldviews, the emerging Rights of Nature movement provides a critical opportunity to re-envision global environmental law through historically colonized and marginalized forms of knowledge. In particular, this article explores the instrumentality of litigation to act as a catalyst for diffusing Southern conceptions in Eurocentric legal cultures to decolonize international law. This article specifically analyzes the animal rights dimension of the broader RoN paradigm. It argues that the recent wave of litigation awarding rights to animals - primarily in the Global South - reflects an evolving inter-judicial dialogue between domestic judges, whose interactions could potentially feed into a cosmopolitan global jurisprudence for animal rights in a bottom-up manner, which captures the plurality of ways of understanding and conceptualizing Nature.